MELALUI SUPERVISI AKADEMIK MODEL ARTISTIK DAPAT MENINGKATAN KEMAMPUAN GURU DALAM MENYUSUN TES SUMATIF DI SDN 020 RAMBAH - Asnita Asnita (JURNAL PENDIDIKAN ROKANIA, 2020)
the purpose of this research is to find out and describe the ability of teachers in compiling summative tests through the academic supervision of artistic models. This study is classified as a school action research involving 10 subject teachers and class teachers, which is used as a sample preparation of summative tests, based on criteria for preparing standardized tests. The study was conducted with 3 (three) cycles. Tests that have been completed are analyzed and assessed based on 3 predetermined parameters, including: 1) aspects of the suitability of the test with learning objectives, 2) aspects of the behavior of the level of difficulty in taxom blom (c1-c6), and to. 3) good and correct use of indonesian on objective tests. Meanwhile, finding out the activities of teachers at work, researchers complete the measuring instrument with observation guidelines. Aspects observed in this activity which are consisted of 5 aspects of teacher activities, such as: a) aspects of the material, b) aspects of activeness, c) aspects of internal presentations, d) aspects of external percentage and e) aspects of the expert panel. Based on the criteria above, from cycle i and cycle iii the average score shows an increase, from an average score of 64.5 to a score of 87.24. It means that the teacher's efforts in preparing the deuteronomy test have been significant and they have put a lot of effort into making a decent test.